1994
DOI: 10.1210/jcem.79.5.7962324
|View full text |Cite
|
Sign up to set email alerts
|

Development of a sensitive two-site immunoradiometric assay for parathyroid hormone-related peptide: evidence for elevated levels in plasma from patients with adult T-cell leukemia/lymphoma and B-cell lymphoma.

Abstract: We have developed a sensitive immunoradiometric assay for PTH-related peptide (PTHrP) using a monoclonal antibody against PTHrP(1-34) and a polyclonal antibody against PTHrP(50-83), with recombinant human PTHrP(1-87) as the standard. The detection limit of the immunoradiometric assay was 0.5 pmol/L, and plasma PTHrP(1-87) concentrations in 110 healthy subjects were 0.8 +/- 0.01 pmol/L, with the upper limit of the normal range being 1.1 pmol/L. Increased circulating PTHrP(1-87) concentrations were demonstrated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 33 publications
1
12
1
1
Order By: Relevance
“…Hypercalcemia ensues only when PTHrP reaches a threshold concentration that replaces and surpasses the analogous actions of PTH. Hypercalcemia attributed to elevated concentrations of humoral PTHrP has been estimated to occur in 33-84% of breast cancers [33][34][35][36][37][38], 46-76% of lung cancers [35,36,38], 21-63% of non-Hodgkin's lymphomas (NHLs) [38][39][40] and 92% of adult T-cell leukemia/ lymphomas due to the human T-lymphotropic virus type 1 (HTLV-1) infection [39]. Infrequently, PTHrPmediated hypercalcemia occurs in head and neck tumors [41,42], renal cell carcinoma [43,44], bladder cancer [45], pancreatic carcinoma [46], hepatocellular carcinoma [47], carcinoid tumors [48] and melanoma [49].…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…Hypercalcemia ensues only when PTHrP reaches a threshold concentration that replaces and surpasses the analogous actions of PTH. Hypercalcemia attributed to elevated concentrations of humoral PTHrP has been estimated to occur in 33-84% of breast cancers [33][34][35][36][37][38], 46-76% of lung cancers [35,36,38], 21-63% of non-Hodgkin's lymphomas (NHLs) [38][39][40] and 92% of adult T-cell leukemia/ lymphomas due to the human T-lymphotropic virus type 1 (HTLV-1) infection [39]. Infrequently, PTHrPmediated hypercalcemia occurs in head and neck tumors [41,42], renal cell carcinoma [43,44], bladder cancer [45], pancreatic carcinoma [46], hepatocellular carcinoma [47], carcinoid tumors [48] and melanoma [49].…”
Section: Signs and Symptomsmentioning
confidence: 99%
“…This topic will be discussed in a later section. Using a sensitive two-site immunoradiometric assay, other investigators have noted increased plasma PTHrP concentrations in patients with adult T cell leukemia and B cell lymphoma (198). PTHrP in hypercalcemia associated with hematological malignancies.…”
mentioning
confidence: 99%
“…Recently, the mechanism for the hypercalcemia in ATL has been elucidated in detail [51][52][53][54][55][56][57][58][59][60][61]. ATL cells secrete an excessive amount of parathyroid hormonerelated peptide (PTHRP) in patients with hypercalcemia [53][54][55][56].…”
Section: Clinical Features/diagnosismentioning
confidence: 99%
“…ATL cells secrete an excessive amount of parathyroid hormonerelated peptide (PTHRP) in patients with hypercalcemia [53][54][55][56]. Ikeda et al [52,57] investigated the molecular mechanism and found that the protein kinase C and protein kinase A pathways are vital in inducing transcription of the PTHRP gene in HTLV-I-infected T cells.…”
Section: Clinical Features/diagnosismentioning
confidence: 99%